Urgensi Kebijakan Publik dalam Penanganan Darurat Bencana: Sebuah Tinjauan Konseptual - Farras Muhammad Nouval; Hayatul Khairul Rahmat (Journal of Current Research in Management, Policy, and Social Studies, 2025)
Indonesia, viewed from a geological and hydrological perspective, is a high-risk area for natural disasters, as it lies at the convergence point of three active tectonic plates, the Indo-Australian Plate. Disaster management is divided into three main stages: (1) pre-disaster, through mitigation and preparedness; (2) emergency response, through evacuation, protection of affected communities, and restoration of vital facilities; and (3) post-disaster, through rehabilitation and reconstruction. Case studies such as the Disaster Preparedness Brigade program in Bantaeng Regency demonstrate the importance of a rapid and organized response in handling emergency situations. However, the implementation of this policy requires consistency in communication, clarity of objectives, and adequate resource support. This paper uses a literature review method to write various institutional and organizational policies for emergency response. Based on the discussion above, it can be concluded that the disaster management policy based on Law Number 24 of 2007 emphasizes mitigation, preparedness, emergency response, and post-disaster recovery. With the institutional policies in emergency response created by stakeholders, it is hoped that through a collaborative approach, thorough planning, and continuous evaluation, Indonesia will be able to increase disaster resilience and minimize its impact on society.